ENHANCE AN UNDERSTANDING OF MICRO SMALL AND MEDIUM ENTITY BOOKKEEPING BASED ON FINANCIAL ACCOUNTING STANDARDS FOR MICRO SMALL AND MEDIUM ENTITIES - Neng Sri Wardhani; Annisa Ilmi Faried; Tia Novira Sucipto; Selfi Widiyanti (Sean Institute, 2023)
UMKM initiatives help create jobs and are very important in assisting Batubara Regency in solving its financial problems to improve the local economy and improve the welfare of its residents, especially in Pahlawan village, Tanjung Tiram District. The purpose of this research is to find out how good the understanding and readiness of UMKM players and the Pahlawan village community in Batubara Regency are to implement UMKM bookkeeping based on Micro, Small and Medium Entity Accounting Standards (SAK UMKM) in 2023, which is beneficial for the continuity of UMKM businesses for business actors. This paper used a sample of 30 people from the village of Pahlawan, Batubara Regency, including UMKM actors. Because this research discusses the understanding of UMKM bookkeeping based on Micro, Small and Medium Entity Financial Accounting Standards in Batubara District, a descriptive qualitative research methodology in the form of words not in the form of numbers is used to present the data in this study.